Distribution, Prevalence, and Antibiotic Susceptibility Profiles of Infectious Noncholera Vibrio Species in Malaysia - Murnihayati Hassan; Mohammad Ridhuan Mohd Ali; Hana Farizah Zamri; Nur Asyura Nor Amdan; Mohammad Noor Amal Azmai; Saraswathiy Maniam; Norfarrah Mohamed Alipiah; Rohaidah Hashim (Journal of Tropical Medicine)
Background. The noncholera Vibrio spp. which cause vibriosis are abundantly found in our water ecosystem. These bacteria could negatively affect both humans and animals. To date, there is a paucity of information available on the existence and pathogenicity of this particular noncholera Vibrio spp. in Malaysia in comparison to their counterpart, Vibrio cholera. Methods. In this study, we extracted retrospective data from Malaysian surveillance database. Analysis was carried out using WHONET software focusing noncholera Vibrio spp. including Vibrio parahaemolyticus, Vibrio vulnificus, Vibrio fluvialis, Vibrio alginolyticus, Vibrio hollisae (Grimontia hollisae), Vibrio mimicus, Vibrio metschnikovii, and Vibrio furnissii. Results. Here, we report the first distribution and prevalence of these species isolated in Malaysia together with the antibiotic sensitivity profile based on the species. We found that V. parahaemolyticus is the predominant species isolated in Malaysia. Noticeably, across the study period, V. fluvialis is becoming more prevalent, as compared to V. parahaemolyticus. In addition, this study also reports the first isolation of pathogenic V. furnissii from stool in Malaysia. Conclusion. These data represent an important step toward understanding the potential emergence of noncholera Vibrio spp. outbreaks.